2022
DOI: 10.4314/njbas.v29i1.7
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Boost-Sepic Higher Static Gain DC-DC Converter for Photovoltaic (PV) Based Micro-Grid Application

Abstract: A new circuit topology is designed for a DC-DC converter. The proposed converter employs a single power switch which integrates a conventional boost with a single-ended primary inductor converter (SEPIC) for photovoltaic (PV) panels. A prototype is developed and implemented for 105 V DC output from 9 V DC input. The performance of the proposed topology was validated using theoretical and practical verification. The results indicated a higher voltage gain of 11.67, low duty-cycle of 0.82 and reduced voltage str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…When compared to conventional converters, this converter offers a number of advantages, including a constant output current supply, minimal output voltage ripple, and minimal current stress. SEPIC Converter is operated in 2 modes: (i) Continuous Current Mode (ii) Discontinuous Current Mode In [6,7] boost and SEPIC converters were paired. It was found that their pairing provides the reduced value of duty cycle along with the extended voltage gain.…”
Section: Figure 1 Circuit Diagram Of Sepic Convertermentioning
confidence: 99%
“…When compared to conventional converters, this converter offers a number of advantages, including a constant output current supply, minimal output voltage ripple, and minimal current stress. SEPIC Converter is operated in 2 modes: (i) Continuous Current Mode (ii) Discontinuous Current Mode In [6,7] boost and SEPIC converters were paired. It was found that their pairing provides the reduced value of duty cycle along with the extended voltage gain.…”
Section: Figure 1 Circuit Diagram Of Sepic Convertermentioning
confidence: 99%